First Principles Calculations of Structural and Elastic Properties of Perovskite Crystals: The Case of SrTiO3. Issue 6 (22nd February 2016) - Pandech, Narasak; Sarasamak, Kanoknan; Limpijumnong, Sukit
Abstract: The structural and elastic properties of perovskite crystals can be independently calculated by using first principles calculations without bias. The detailed calculation of cubic perovskite ( Pm 3 m ) crystal by first‐principles calculations both LDA and GGA approaches was shown, using SrTiO3 as an illustration case. The equilibrium volumes and bulk modulus of SrTiO3 were evaluated by fitting to Birch‐Murnaghan equation of states. The C 11, C 12, and C 44 elastic constants were obtained from a polynomial fit to the calculated energy‐strain relations. For SrTiO3, the calculated lattice constants, bulk modulus, and all three elastic constants by both LDA and GGA calculations are in good agreement with experimental values. Because LDA gives a slightly smaller lattice constant compared to that obtained from GGA, the bulk modulus and all three elastic constants obtained from LDA are slightly larger than those values obtained from GGA. The calculation steps illustrated here can be used as a guideline to study elastic properties of other novel materials. Abstract : This manuscript shows step‐by‐step computation of structural and elastic properties of a cubic crystal by first principles approach (using cubic perovskite SrTiO3 as an illustration case). The calculated values are in a reasonable agreement with the experimental values indicating that the approach is highly reliable and can be used for novel materials.